THE TRANSLATION METHODS APPLIED IN VIETNAMESE VERSION OF THE ADVENTURES OF TOM SAWYER BY MARK TWAIN = Các phương pháp dịch được áp dụng trong bản dịch tiếng Việt của tác phẩm những cuộc phiêu lưu của Tom Sawyer – tác giả Mark Twain - Nguyễn, Duy Tuấn (2020)
Though The Adventures of Tom Sawyer is one of excellent works by Mark Twain, which has great impacts on American literature, there have been little to no research on the way professional translators translate it into Vietnamese. As an attempt to gain more insights into translation methods in literary translation, this research aims to investigate the translation methods used by the two translators Nguy Mong Huyen and Hoang Van Phuong in translating The Adventures of Tom Sawyer into Vietnamese. Besides that, the research succeeds in identifying the frequency of every translation methods as well as their effectiveness. Finally, some suggestions would also be given. These goals were achieved by a research using questionnaire and document observation. Questionnaire were delivered to all 4th year students majoring in Translation and Interpreting, FELTE, ULIS, VNU. Findings from the study show that there are up to 6 out of 8 translation methods according to Peter Newmark’s theory being used throughout the story The Adventures of Tom Sawyer. The most common translation method applied is communicative translation – a surprise to the researcher as the most appropriate method which are usually used in literary works is semantic translation method. The study also suggests a non-traditional point in translating literary works. Moreover, the researcher also suggest some better issues for further research.